Implementasi Peran Fasilitator Pendampingan pada Komunitas Single Mother di Perumahan Arbain Kecamatan Bangil Kabupaten Pasuruan - Ulin Fauziah; Widya Nusantara (J+PLUS UNESA, 2023)
The purpose of this study was to analyze and describe the implementation of the role of mentoring fasilitators in the single mother community in Arbain Housing, Bangil District, Pasuruan Regency. The research method used in this research is descriptive qualitative. The result show the various forms of activity (1) The form of the facilitating role consist of activities of social enthusiasm, group facilitation, and support (2) The form of the educating role consist of activities using the media, obtaining various resources and building networks (3) The form of the technical role consist of financial regulatory activities. Furthermore, the factors that support of the role of facilitator include completeness of infrastructure and commitment to harmony and obedience to regulations. Meanwhile, the factors that hinders of the role is the lack of government support and the presence of community members who are less proactive.